1990
DOI: 10.1111/j.1151-2916.1990.tb06752.x
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Filtration and (Simultaneous) Sedimentation of Alumina and Silica Suspensions: Influence of Aggregates

Abstract: Colloidal filtration and (simultaneous) sedimentation is studied for suspensions of alumina particles and monodisperse silica spheres. A comparison is made between stable suspensions and systems which are aggregated due to salt addition (silica) or absence of a deflocculant (alumina). From separate sedimentation experiments we conclude that the stable silica settles as an ordered particle array, that the unstable silica sediments as separate aggregates, and that aggregated alumina behaves as a densifying netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…18 The densities of consolidated powder compacts were measured by the Archimedes method using kerosene. % A1 2 O 3 , 24.0 wt.…”
Section: Methodsmentioning
confidence: 99%
“…18 The densities of consolidated powder compacts were measured by the Archimedes method using kerosene. % A1 2 O 3 , 24.0 wt.…”
Section: Methodsmentioning
confidence: 99%
“…Above some critical volume fraction, known as the gel point ( g ), the clusters become overcrowded and an inhomogeneous space-filling network (or gel) forms, which may or may not sediment depending on its strength. 13 Philipse et al 14 have studied colloidal filtration of relatively dilute, aggregated silica suspensions and shown that simultaneous aggregate sedimentation leads to deviations from the known linear relationship between compact thickness and the square root of the filtration time as well as a decrease in process time. Carpineti et al 15 have studied fast, salt-induced colloidal aggregation phenomena, and shown that growth from dilute systems ceases because of sedimentation when clusters reach some maximum size.…”
Section: Introductionmentioning
confidence: 99%
“…To derive the √ t-scaling relation for growing packings in the experiments described in this study, we briefly review the derivation reported in Ref. [36]. We consider the situation as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4(a) shows a typical plot measured during the formation of a packing. Unlike for flow through a packing of constant thickness, the permeated mass through a growing packing does not grow linearly in time due to the increase of the hydrodynamic friction during packing formation [7,19,36]. From the derivation described in Appendix A, it follows that for a growing, incompressible and homogeneous packing, the permeated solvent mass W scales with the square root of the time t rather than with t according to…”
Section: A Packing Formationmentioning
confidence: 99%
See 1 more Smart Citation